Mind mapping in recalling and retrieving core contents in anesthesia technology students - Atiyeh S Sajadi; Parisa Moradi Majd; Shahnam Sedigh Maroufi; Jamileh Abolghasemi (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Human memory represents the ability to recall and retrieve information. Learning methods have a great impact on remembering and retrieving material. This study was conducted to investigate the effect of the mind map learning method on the amount of recall and retrieval of the core contents of anesthesia technology students. MATERIALS AND METHODS: In this quasi-experimental study, 55 undergraduate students of anesthesia technology were included in the study by census method. In both groups, teaching was done in the same way (lecture method) by a single professor. The intervention group was randomly divided into six groups. After training to work with a mind map in this group, the teaching of lessons started with the lecture method, and then the mind map was drawn by the group members. In the control group, the students followed the lecture method and note-taking. Finally, three tests were taken. Test 1 (before the start of the training), test 2 (immediately after the training (scheduled test)), and test 3 (after 2 weeks (surprise test)). RESULTS: The data obtained from the test scores were analyzed by paired t-test, independent t-test, and analysis of covariance. The analysis showed that the mind map method significantly improved the short-term (P < 0.001) and long-term memory of anesthesia technology students (P < 0.001) compared to the traditional method. Examining the effect of gender on long-term memory showed that in the intervention group, female samples had an average score of 1 more than male samples (P = 0.044). DISCUSSION: It seems that mind mapping improves short-term and long-term memory in anesthesia technology students who play a critical role in saving the lives of patients and this issue improves the quality of services in the field of health.